Effects of combined oral contraceptives and metformin on paraoxonase 1 lactonase activity and status in patients with polycystic ovary syndrome and insulin resistance - Liang, Jiagui; Wang, Qiuyi; Liu, Dong; Wu, Lukanxuan; Qiao, Xinyu; Wang, Ruiying; Zhong, Yuchan; Bo, Wenjie; Lai, Huiqiao; Fan, Ping; Huang, Wei (Frontiers in Endocrinology, 2026)
ObjectiveTo investigate the effects of combined oral contraceptives (COCs) and metformin treatment on the lactonase activity and status of paraoxonase 1 (PON1), and oxidative stress levels in patients with polycystic ovary syndrome (PCOS) and insulin resistance (IR).DesignA prospective, self-controlled study.MethodsSixty patients diagnosed with PCOS and IR underwent three months of comprehensive therapy, including lifestyle modification, oral metformin (1000–1500 mg/day), and a COC (3 mg drospirenone and 20 µg ethinyl estradiol). Clinical data and blood samples were collected at baseline and after three months of treatment. PON1 levels, lactonase activity, and normalized lactonase activity (NLA), along with PON1 Q192R and C-108T genetic polymorphisms, oxidative stress markers, hormonal profiles, and metabolic parameters, were analyzed.ResultsAfter treatment, significant decreases were observed in body mass index (BMI), Global Acne Grading System scores, androstenedione, fasting insulin, the homeostasis model assessment of insulin resistance index, and total antioxidant capacity (P < 0.05). In contrast, serum PON1 lactonase activity, apolipoprotein (apo)A1, triglycerides, and 2-h glucose levels were significantly increased (P < 0.05). Spearman’s correlation analysis showed that lactonase activity and PON1 status were correlated with serum apoA1, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol, total oxidant status, and the oxidative stress index (P < 0.05). Moreover, the group with improved NLA showed higher PON1 lactonase activity and HDL-C levels, whereas the group without improved NLA showed higher PON1 levels after treatment.ConclusionTreatment with COCs and metformin enhanced the antioxidant capacity of circulating HDL and improved BMI, glycolipid metabolism, IR, and hyperandrogenism in patients with PCOS and IR.Clinical Trial Registrationhttps://www.chictr.org.cn/showproj.html?proj=152682, identifier ChiCTR2200057114.